The Essence, Principles and Foundation of Curriculum Development - Oktaviana, Shella; Saputra, Rikky Triolin; Hadiati, Eti; Ayu, Sovia Mas; Fauzan, Ahmad (IJoIS: Indonesian Journal of Islamic Studies, 2024)
This study aims to explain the nature, principles and foundation of curriculum development that plays a role in shaping the goals and direction of education in schools in Indonesia. This type of research is library research, which is a series of activities related to literature. The writing method used is descriptive qualitative. Primary reference sources are reading and recording and processing research materials in libraries such as books, news, and others. In accordance with the title of the researcher lift, then this study uses a qualitative approach. The results showed that the development of an effective curriculum must take into account a variety of interrelated factors, including the philosophy of education, the philosophy of the state, the development of society and culture, psychological aspects, science and technology, as well as religious values.